Step On It! Impact of a Workplace New York City Taxi Driver Health Intervention to Increase Necessary Health Care Access - Gany, Francesca (Am J Public Health, 2015)
Objectives. We describe the impact of the Step On It! intervention to link taxi drivers, particularly South Asians, to health insurance enrollment and navigate them into care when necessary. Methods. Step On It! was a worksite initiative held for 5 consecutive days from September 28 to October 2, 2011, at John F. Kennedy International Airport in New York City. Data collected included sociodemographics, employment, health care access and use, height, weight, blood pressure, and random plasma glucose. Participants were given their results, counseled by a medical professional, and invited to participate in free workshops provided by partner organizations. Results. Of the 466 drivers participated, 52% were uninsured, and 49% did not have a primary care provider. Of 384 drivers who had blood pressure, glucose, or both measured, 242 (63%) required urgent or regular follow-up. Of the 77 (32%) requiring urgent follow-up, 50 (65%) sought medical care at least once, of whom 13 (26%) received a new diagnosis. Of the 165 (68%) requiring regular follow-up, 68 (41%) sought medical care at least once, of whom 5 (7%) received a new diagnosis. Conclusions. This study provides encouraging results about the potential impact of an easy-to-deliver, easily scalable workplace intervention with a large, vulnerable population.